The host galaxies and explosion sites of long-duration gamma-ray bursts: Hubble Space Telescope near-infrared imaging - Lyman, D.J.; Levan, A.J.; Tanvir, N.R.; Fynbo, J.P.U.; McGuire, J.T.W.; Perley, D.A.; Angus, C.R.; Bloom, J.S.; Conselice, Christopher J.; Fruchter, A.S.; Hjorth, J.; Jakobsson, P.; et al. (Oxford University Press, 2017)
We present the results of a Hubble Space Telescope WFC3/F160W Snapshot survey of the host galaxies of 39 long-duration gamma-ray bursts (LGRBs) at z < 3. We have non-detections of hosts at the locations of four bursts. Sufficient accuracy to astrometrically align optical afterglow images and determine the location of the LGRB within its host was possible for 31/35 detected hosts. In agreement with other work, we find the luminosity distribution of LGRB hosts is significantly fainter than that of a star formation rate-weighted field galaxy sample over the same redshift range, indicating LGRBs are not unbiasedly tracing the star formation rate. Morphologically, the sample of LGRB hosts is dominated by spiral-like or irregular galaxies. We find evidence for evolution of the population of LGRB hosts towards lower luminosity, higher concentrated hosts at lower redshifts. Their half-light radii are consistent with other LGRB host samples where measurements were made on rest-frame UV observations. In agreement with recent work, we find their 80 per cent enclosed flux radii distribution to be more extended than previously thought, making them intermediate between core-collapse supernova (CCSN) and superluminous supernova (SLSN) hosts. The galactocentric projected-offset distribution confirms LGRBs as centrally concentrated, much more so than CCSNe and similar to SLSNe. LGRBs are strongly biased towards the brighter regions in their host light distributions, regardless of their offset. We find a correlation between the luminosity of the LGRB explosion site and the intrinsic column density, NH, towards the burst.